Voltaire’s Ambivalent Representation of Islam: An Intellectual History Analysis of the XVIII Century Enlightenment - Ahmad Al Ghiffari Tauhid; Ajid Thohir; Fathia Lestari (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
Voltaire’s critical stance toward religion constitutes a controversial discourse within Enlightenment intellectual history, particularly regarding his satirical critiques of religious dogma and clerical institutions. However, his position on Islam reveals a unique, non-monolithic characteristic that has rarely been examined as a central theme in Voltaire scholarship. Utilizing the Historical method with an Intellectual History approach, this study conducts a descriptive textual analysis by identifying, classifying, and synthesizing textual representations of Voltaire’s ambivalence toward Islam across his corpus within the eighteenth-century intellectual context. The findings indicate that critique and appreciation coexisted simultaneously without a linear chronology, showing no significant shift in his attitude throughout his career. This study challenges previous discourses that have tended to position Voltaire within a dichotomous or chronological framework, offering a more nuanced analytical model that enriches Voltaire scholarship and intellectual history by showing how conflicting representations coexist within a single corpus.